Uric Acid—An Emergent Risk Marker for Thrombosis? - Țăpoi, Laura (J Clin Med, 2021)
Hyperuricemia is nowadays an established cardiovascular risk factor. Experimental studies linked elevated serum uric acid (SUA) levels with endothelial dysfunction (ED), inflammation, and prothrombotic state. The purpose of this review is to summarize the current evidence that emphasizes the possible role of uric acid as a biomarker for a prothrombotic state. A large number of clinical trials correlated SUA levels with both incident and recurrent cases of venous thromboembolism (VTE), independent of other confounding risk factors. Moreover, increased SUA levels may be an important tool for the risk stratification of patients with pulmonary embolism (PE). Left atrial thrombosis was correlated with high SUA levels in several studies and its addition to classical risk scores improved their predictive abilities. In patients with acute myocardial infarction (MI), hyperuricemia was associated with increased mortality, and the idea that hyperuricemia may be able to act as a surrogate to unstable coronary plaques was advanced. Finally, SUA was correlated with an increased risk of thromboembolic events in different systemic diseases. In conclusion, uric acid has been considered a marker of a thrombotic milieu in several clinical scenarios. However, this causality is still controversial, and more experimental and clinical data is needed.